2011
DOI: 10.1017/s1368980011002011
|View full text |Cite
|
Sign up to set email alerts
|

The public health nutrition intervention management bi-cycle: a model for training and practice improvement

Abstract: Objective: The present paper describes a model for public health nutrition practice designed to facilitate practice improvement and provide a step-wise approach to assist with workforce development. Design: The bi-cycle model for public health nutrition practice has been developed based on existing cyclical models for intervention management but modified to integrate discrete capacity-building practices. Setting: Education and practice settings. Subjects: This model will have applications for educators and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
1
20
0
2
Order By: Relevance
“…The results from this student sample suggest that research, evaluation and broader professional competency development is enriched by learning and teaching interventions that expose students to the complete research and evaluation practice cycle, with a summative assessment focus based on preparation of a journal manuscript. This reinforces arguments from public health nutrition educators about the merits of experiential learning using action research models …”
Section: Discussionsupporting
confidence: 65%
“…The results from this student sample suggest that research, evaluation and broader professional competency development is enriched by learning and teaching interventions that expose students to the complete research and evaluation practice cycle, with a summative assessment focus based on preparation of a journal manuscript. This reinforces arguments from public health nutrition educators about the merits of experiential learning using action research models …”
Section: Discussionsupporting
confidence: 65%
“…Numerous programs identified opportunities for sustainability, such as linking community kitchens with community gardens. Adequate workforce capacity is an essential element for the success of public health nutrition initiatives (Hughes and Margetts 2012). The present study demonstrated the need to consider workforce capacity when planning CFPs.…”
Section: Discussionmentioning
confidence: 77%
“…Desse modo, conforme apontado pelas análises dos planos de ensino das disciplinas na área de nutrição em saúde coletiva, a descrição dos cursos de Nutrição, de acordo com seus projetos político-pedagógicos, apresenta, quase em sua maioria, a mesma forma para tratar de alguns poucos conteúdos que se diferenciam. Países como a Austrá-lia, Canadá, Suécia, dentre outros, têm tentado minimizar esses desafios nos seus planos pedagógicos 5,[18][19][20] Outro resultado apresentado neste estudo foi a pequena relação encontrada entre as três categorias (competências esperadas, ações realizadas no cuidado nutricional e operacionalização do curso). É possível sugerir que os conteúdos dos projetos político-pedagógicos estão diferenciados pelo quanto estão assimilados aos conteúdos da primeira classe (tratamento) e da segunda classe (prevenção e promoção).…”
Section: I S C U S S ã Ounclassified